Pendapat Imam Mazhab terhadap Mahar Mitsil Bukan Merupakan Syarat Kafa’ah - Hidayatus Saadah Lubis; Tamara Sofa; Nur Fatimah Azzahra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Mahar mitsil is a mahar that is not determined at the time of the marriage contract, but is adjusted to the value usually received by the wife's family. This study aims to examine the opinions of the imams of the madhhab regarding mahar mitsil not being a condition for kafa'ah. This study discusses how to apply mahar mitsil so that it does not become a condition for kafa'ah. The research method in this article is empirical juridical. By using an empirical juridical approach, this study examines theories, concepts, and the Quran and Hadith related to mahar mitsil. Mahar mitsil according to Imam Syafi'i and Imam Maliki is not a condition for kafa'ah. Kafa'ah here is more related to equality in terms of religion and lineage. While mahar mitsil according to Imam Hanafi is part of the conditions for kafa'ah. However, mahar is very important, although mahar does not become a barrier to the validity of the marriage contract if the conditions for marriage are met.